The organic coating unit, an all-in-one system for reproducible generation of secondary organic matter aerosol. Issue 10 (6th September 2022) - Keller, Alejandro; Kalbermatter, Daniel M.; Wolfer, Kate; Specht, Patrik; Steigmeier, Peter; Resch, Julian; Kalberer, Markus; Hammer, Tobias; Vasilatou, Konstantina
Abstract: We report on a novel automated oxidation flow reactor to generate a wide variety of organic aerosol samples. The instrument is equipped with a humidifier, a dosing system for volatile organic precursors and an oxidation flow reactor (OFR) for generation of secondary organic matter (SOM). The instrument, known as organic coating unit (OCU), can produce homogeneously nucleated SOM particles or, used in combination with a standard combustion generator (e.g., a diffusion flame soot generator or any other seed particle), particles coated with a controlled amount of SOM. The physical and chemical properties of the generated particles can be controlled in a simple manner by selecting through a touch-screen target values for parameters, such as organic gaseous precursor concentration, humidity, and UV (ultraviolet) light intensity. Parameters and measured quantities are automatically stored in text files for easy export and analysis. Furthermore, we provide stable operation conditions and characterize the physicochemical properties of the generated aerosols with an array of methods, including transmission electron microscopy (TEM), thermal-optical analysis and liquid chromatography coupled with mass spectrometry (LC-MS). This all-in-one instrument is robust, compact, portable, and user-friendly, making it ideal for laboratory or field-based aerosol studies.